Synthesis and Characterization of a Novel Triangular Rh2Au Cluster Compound Inspired by the Isolobality Concept. Issue 10 (5th October 2020) - Böttcher, Hans‐Christian; Graf, Marion; Mayer, Peter; Scheer, Manfred
Abstract: The synthesis of [Rh2 (η 5 ‐Cp)2 (μ‐H)(μ‐PPh2 )2 ]BF4 (2 ) by protonation reaction of the metal basic complex [Rh2 (η 5 ‐Cp)2 (μ‐PPh2 )2 ] (1 ) with tetrafluoroboric acid in diethyl ether is described. Complex salt 2 was obtained in high yield and fully characterized by spectroscopic means and X‐ray crystal diffraction. Applying the isolobal analogy between H and the fragment Au(PPh3 ) as a synthetic strategy on the reaction of compound 2 with equimolar amounts of [Au(CH3 )(PPh3 )] in refluxing acetone resulted in the formation of the expected triangular cluster compound [Rh2 μ‐Au(PPh3 )(η 5 ‐Cp)2 (μ‐PPh2 )2 ]BF4 (3 ) in good yield. Metal cluster salt 3 was fully characterized by spectroscopic data and its molecular structure in the crystal was determined by X‐ray diffraction. The structural comparison of the protonated dirhodium core in the cationic complex of 2 with the Rh2 Au framework in 3 is in good accordance with the isolobal relation between H + and Au + because they share the respective same position in these closely related molecular structures. Abstract : The structural comparison of the metal cores of two new crystallographically characterized compounds [Rh2 (η 5 ‐Cp)2 (μ‐H)(μ‐PPh2 )2 ]BF4 (2) and [Rh2 μ‐Au(PPh3 )(η 5 ‐Cp)2 (μ‐PPh2 )2 ]BF4 (3) confirmed the validity of the isolobal relationship between the fragments H and Au(PPh3 ).